2004
DOI: 10.1620/tjem.204.63
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Cardiac Autonomic Regulation in Children with Monosymptomatic Nocturnal Enuresis by Analysis of Heart Rate Variability

Abstract: The pathogenesis of monosymptomatic nocturnal enuresis is controversial. Various urodynamic studies showed bladder hyperactivity in enuretic children. But the exact cause is not precisely known. The aim of this study was to understand whether the autonomic nervous system dysfunction is involved in this bladder hyperactivity or not. Heart rate variability measurement is widely used for evaluation of cardiac autonomic activity. We evaluated cardiac autonomic nervous system functions in monosymptomatic nocturnal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 24 publications
0
25
0
3
Order By: Relevance
“…Indeed, decrease in HRV was suggested to predict coronary heart disease morbidity and mortality in patients after an acute coronary event (Odemuyiwa et al 1991). Moreover, HRV parameters were found to be altered in various disorders such as diabetic neuropathy (Kitney et al 1982), heart failure (Saul et al 1988), acute leukemias (Nevruz et al 2007), allergic rhinitis , fetal type Minamata disease (Oka et al 2002), in preschool children with short nocturnal sleep (Sampei et al 2006), primary nocturnal enuresis (Dundaroz et al 2001;Unalacak et al 2004), following a cardiac transplantation (Sands et al 1989) or cardiac resynchronization therapy (Akyol et al 2006) and during adrenocorticotropic hormone replacement treatment in infants with West syndrome (Hattori et al 2007). Veglio et al (1998) reported decreased sympathetic activity in patients with thalassemia major.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, decrease in HRV was suggested to predict coronary heart disease morbidity and mortality in patients after an acute coronary event (Odemuyiwa et al 1991). Moreover, HRV parameters were found to be altered in various disorders such as diabetic neuropathy (Kitney et al 1982), heart failure (Saul et al 1988), acute leukemias (Nevruz et al 2007), allergic rhinitis , fetal type Minamata disease (Oka et al 2002), in preschool children with short nocturnal sleep (Sampei et al 2006), primary nocturnal enuresis (Dundaroz et al 2001;Unalacak et al 2004), following a cardiac transplantation (Sands et al 1989) or cardiac resynchronization therapy (Akyol et al 2006) and during adrenocorticotropic hormone replacement treatment in infants with West syndrome (Hattori et al 2007). Veglio et al (1998) reported decreased sympathetic activity in patients with thalassemia major.…”
Section: Discussionmentioning
confidence: 99%
“…Decrease in HRV has been found to predict coronary heart disease morbidity and mortality in apparently healthy populations and in patients after an acute coronary event (Akselrod et al 1981). There has been a large scale growth in HRV research in disease states such as diabetic neuropathy (Bernardi et al 1992), cardiac transplantation (Sands et al 1989), myocardial dysfunction (Casolo et al 1989), tetraplegia (Inoue et al 1990), preschool children with short nocturnal sleep (Sampei et al 2006), primary nocturnal enuresis (Dundaroz et al 2001;Unalacak et al 2004), allergic rhinitis (Yokusoglu et al 2007), fetal type Minamata disease (Oka et al 2003), administration of beta blockers (Adamson et al 1994), cardiac resynchronization therapy (Akyol et al 2006), antiarrhytmics (Zuanetti et al 1991) and scopolamine (De Ferrari et al 1993). However, the impact of HRV on clinical decisions is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Also, it has been suggested that subjects with low HRV had an adverse cardiovascular risk profile and an elevated risk of incident CHD and death (Dekker et al 2000), and that cardiovascular autonomic function played an important role in increasing blood pressure levels associated with increased modulation of parasympathetic tone of the heart after puberty but not in preadolescents (Tanaka et al 2000). In this way, HRV is thought to be a promising and reliable tool to provide a marker of less favorable health (Grandjean et al 2004;Unalacak et al 2004;Murata et al 2006), and this approach should be applied to sleep research in children.…”
Section: © 2006 Tohoku University Medical Pressmentioning
confidence: 99%